"Testosterone decreases temporomandibular joint nociception"— A systematic review of studies on animal models. (July 2022) - Javed, Fawad; Ahmed, Hameeda Bashir; Zafar, Muhammad Sohail; Shaikh, Muhammad Saad; Rossouw, P. Emile; Michelogiannakis, Dimitrios; Alstergren, Per
Abstract: Objective: The aim of the present systematic review was to assess the effect of testosterone on temporomandibular joint (TMJ) nociception. Design: A systematic review of pertinent indexed literature was performed. The focused question addressed was "Is there a connection between testosterone and TMJ nociception?" Original studies were included. In-vitro and ex-vivo studies, case-reports/series, letters to the Editor and commentaries were not sought. Indexed databases were searched without time and language restrictions up to and including September 2021 using different free text key words: testosterone OR "male sex hormones" OR "gonadal hormones" AND "temporomandibular joint" OR "temporomandibular dysfunction" AND nociception AND males. The literature search was performed in accordance with the preferred reporting outcomes of systematic reviews and meta-analysis guidelines. The risk of bias (RoB) was assessed using the SYstematic Review Centre for Laboratory animal Experimentation (SYRCLE) tool. Results: Out of the 406 studies identified, seven studies on animal-models were included. All studies were performed in rats with age and weight ranging between 21 and 90 days and 200–300 g, respectively. Testosterone was administered in concentrations ranging between 1 and 10 mg/Kg. Results from all studies showed that testosterone administration in gonadectomized male rats reduces induced TMJ nociception. The RoB was high in 3 and unclear in 4 studies. Conclusion: Testosterone offers protection against TMJ nociception in male rats; however, from a clinical perspective, potential contribution of testosterone therapy towards the management of TMD remains indeterminate. Highlights: Seven studies performed in gonadectomized male and female rats were included. Testosterone was administered in concentrations ranging between 1 and 10 mg/Kg. In six studies, TMJ nociception was induced via subcutaneous formalin injections. In one study, TMJ nociception was induced by Complete Freud's Adjuvant injection. Testosterone administration reduced TMJ nociception in gonadectomized rats.